The Possibilities for Enhancing Ownership of Development in Africa: the role of regional integration in the external relations of Africa - Mah, L.; Freitas, R. (WP CESA, 2012)
Africa has been the neglected continent in world politics. It has also been the subject of aid dependency and policy conditionality, leaving little autonomy of decision-making and ownership of its development policies. The recent economic turn-around and the global rush for resources and commodities have raised the importance of the African continent in the international economic scene. Many African countries are rich in resources and they have seen their development possibilities enhanced by intensified economic relations in particular with the emerging economies but also with their traditional main partners. However, as this is happening at the country level and African countries still have disperse voices in their exchanges with the rest of the world, the possibilities for leveraging this new potential are limited. Through the analysis of the dynamics of regional integration in Africa, this paper explores the hypothesis that increased integration would give a stronger voice, policy space and ultimately ownership of policies to African countries.